2020
DOI: 10.34172/mj.2020.020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 12 weeks of Pilates Training on the Serum Levels of Interleukin-6, C - reactive protein and Tumor Nerosis Factor-α in Inactive Overweight Women

Abstract: Background: Increasing inflammatory markers of CRP, TNF-α and IL-6 leads to increasing cardiovascular disease. Change in lifestyle represents a successful strategy to prevent cardiovascular disease. The purpose of this study was to investigate the effect of 12 weeks Pilates training on serum levels of IL-6, CRP and TNF-α in inactive overweight women.Methods: In this quasi-experimental study 28 volunteer overweight women (with average BMI of 27.2, 1.1 ± kg/m 2 ) participated. They were randomly divided into tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 24 publications
4
5
0
Order By: Relevance
“…Our results show that Pilates practitioners displayed lower CRP levels than controls at baseline, suggesting long-term participation may reduce levels of this acute inflammatory marker. This finding supports previous data that Pilates training can significantly reduce serum CRP levels (Khajehlandi et al, 2020). On the contrary, it has been reported that a 20-week Pilates intervention has no effect on serum CRP levels in elderly individuals (Pestana et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…Our results show that Pilates practitioners displayed lower CRP levels than controls at baseline, suggesting long-term participation may reduce levels of this acute inflammatory marker. This finding supports previous data that Pilates training can significantly reduce serum CRP levels (Khajehlandi et al, 2020). On the contrary, it has been reported that a 20-week Pilates intervention has no effect on serum CRP levels in elderly individuals (Pestana et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…Still, it is against the findings of Jones et al [30] and Kang et al [31]. The decrease in body fat percentage and the decrease in serum level of resistin may be related to the body's physiology in response to the type and duration of exercise [24]. In the study by Jones et al [30], who examined the effect of 16 weeks of aerobic exercise with an intensity of 50%-85% maximum oxygen consumption, no weight loss was observed, but a decrease in body fat percentage was reported.…”
Section: Discussionmentioning
confidence: 79%
“…To influence the body fat percentage, the intensity and duration of exercise should be considered so that fatty acids are used as a source of energy. The discrepancy between results may be the difference in duration/intensity/type of exercise and gender [24], which are factors affecting the production of resistin.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The impact of PT on hematological and biochemical variables has recently become a new field of investigation. It has been demonstrated that PT has a beneficial impact on adipokine levels in overweight women when used for 12 weeks, three days per week for 60 minutes [ 13 ] , as well as serum levels of certain inflammatory markers such as C reactive protein in sedentary women with overweight [ 14 ] . Researchers have also shown that PT is a suggested physical activity to promote health and boost the immune system [ 15 , 16 ] .…”
Section: Introductionmentioning
confidence: 99%